Efficacy of Alfuzosin in Male Patients with Moderate Lower Urinary Tract Symptoms: Is Metabolic Syndrome a Factor Affecting the Outcome? - Sonmez, Gokhan; Topaloglu, Ulas Serkan; Keske, Murat; Demirtas, Abdullah (Urology Journal, 2020)
Purpose: The present study was designed to compare the efficacy of alfuzosin therapy as an alpha-blocker in metabolic syndrome (MetS) and non-MetS patients with moderate lower urinary tract symptoms (LUTS). Material and Methods: This prospective study included male patients with obstructive voiding and had a moderate LUTS according to International Prostate Symptom Score (IPSS). Patients were divided into two groups: MetS and Non-MetS. Following the measurement of uroflowmetric parameters (maximum flow rate [Qmax], post-void residual volume [PVR], urine volume) and the determination of IPSS scores, the patients were initiated on alfuzosin 10 mg once daily for a period of 12 weeks. At the end of the therapy, treatment outcomes were determined based on uroflowmetric parameters and IPSS scores. Results: 301 patients were included in the study (MetS: 160, non-MetS: 141). Pre-treatment uroflowmetric measurements and IPSS scores were similar in both groups. After the therapy, the median Qmax level increased from 12.80 (10.62-14.82) ml/s to 14.55 (12.00-16.60) ml/s in the MetS group and from 12.60 (8.60-14.60) ml/s to 15.70 (13.20-17.20) ml/s in the non-MetS group (p<0.001 for both). Similar statistically significant changes were valid for PVR and IPSS. Post-treatment Qmax, PVR values and IPSS scores were higher in the non-MetS patients compared to MetS patients. Conclusion: Although the non-MetS patients had greater benefit from the alfuzosin therapy compared to the MetS patients, alfuzosin is an effective alpha-blocker in the treatment of MetS patients with moderate LUTS. Based on these findings, it is tempting to consider that MetS might be a negative factor for benign prostate hyperplasia treatment.